ANALISIS KONTRIBUSI SEKTOR PARIWISATA TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN NGADA - Maria B.D.B. Roga; Selfesina Samadara; Zainudin A. Djaha (P3M- Politeknik Negeri Kupang, 2019)
This study is entitled Analysis of the Contribution of the tourism Sector to the Ngada Regency’s Original Revenue (Case Study at the Ngada Regency Tourism and Culture Office). This study aims to determine the Contribution of Tourism to the Original Revenue of Ngada Regency. The type of data in this study is quantitative data in the form of tourism, retribution and original income data of the Ngada district in the 2015 to 2018 fiscal year. Based on the results of the analysis obtained from 2015 to 2018 there were 10 attractions, namely the Bena traditional vilage, the Tololela traditional vilage, Gurusina traditional vilage, Wogo traditional vilage, Bela traditional vilage, Soa hot spring, 17 island marine park, Wawomudha lake, Malanage hot spring, Boba Soka hot spring. The contribution of the tourism sector to the Ngada distrit’s original revenue in 2015 was 0,92%, in 2016 it was 1,6%. The result of the analysis carried out it can be concluded of the tourism sector to local revenue in Ngada district with an average presentation rate of 1,06%.